Perverse politics? Feminism, anti-imperialism, multiplicity - Orloff, Ann Shola 1953-; Ray, Raka; Savci, Evren (Emerald, 2016)
In this special issue, we address what we refer to as 'perversity of the political' or 'perverse politics': namely, the assumptions political theory and movements, and in our specific case feminism, often make on behalf of their subjects, and how their subjects, in return, perform individual and collective contrariness, unruliness and resistance to what is expected or desired from their 'subjectivity'. Specifically focusing on the themes of 'false consciousness', multiplicity, and uneasy alliances, the papers collected here seek to empirically lay out a number of such 'perverse' moments, and offer anti-imperialist feminist alternatives to second wave feminism's often reductive understandings of freedom; emancipation; oppression; empowerment and democracy
Literaturangaben
Keywords: Feminism / Political aspects; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Politik; Antiimperialismus; Feminismus; Sozialpolitik; Aufsatzsammlung